VD_FINDINFO HC / 2014 / 88 vom 9. Januar 2014 - VD Tribunal cantonal (2014)
DROIT DE GARDE, MESURE PROVISIONNELLE, DIVORCE, VISITE, MODIFICATIONEN GÉNÉRAL | 176 al. 3 CC, 179 al. 1 CC, 273 al. 1 CC, 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH)